The Role of Digital Marketing Strategies in Enhancing Financial Performance Through Consumer Loyalty: A Case Study of Darbe Café, Surabaya - Janantya, Mario Rama (Syntax Corporation, 2026)
The rapid development of digital technology has transformed marketing practices, particularly for small and medium enterprises (SMEs) seeking to enhance competitiveness through social media and influencer collaboration. However, the effectiveness of digital marketing strategies in shaping consumer trust, engagement, and loyalty remains uneven, especially when influenced by demographic factors such as educational background. This study aims to examine the role of digital marketing strategies in improving financial performance through consumer loyalty, with a focus on the mediating roles of trust and engagement. This research employs a quantitative approach using a structured experimental design involving 150 respondents who were exposed to influencer-generated content. Data were collected through a Likert scale questionnaire and analyzed using composite score calculations to evaluate consumer perceptions of trust, engagement, and loyalty. The findings reveal that digital marketing strategies significantly influence consumer behavior, with influencer credibility and content authenticity playing a crucial role in strengthening trust and engagement. Education level was found to moderate these relationships, with highly educated consumers exhibiting stronger trust, higher engagement, and greater loyalty. Furthermore, trust and engagement function as mediating variables linking digital marketing efforts to purchasing decisions and long-term loyalty. In conclusion, effective digital marketing strategies that emphasize authenticity, transparency, and audience segmentation can enhance consumer loyalty and improve SME financial performance in a competitive digital environment.